2008
DOI: 10.5194/acp-8-7087-2008
|View full text |Cite
|
Sign up to set email alerts
|

1-D Air-snowpack modeling of atmospheric nitrous acid at South Pole during ANTCI 2003

Abstract: Abstract.A 1-D air-snowpack model of HONO has been developed and constrained by observed chemistry and meteorology data. The 1-D model includes molecular diffusion and mechanical dispersion, windpumping in snow, gas phase to quasi-liquid layer phase HONO transfer and quasi-liquid layer nitrate and interstitial air HONO photolysis. Photolysis of nitrate is important as a dominant HONO source inside the snowpack, however, the observed HONO emission from the snowpack was triggered mainly by the equilibrium betwee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 43 publications
3
31
1
Order By: Relevance
“…Treatment of photochemistry in surface snow and ice has focused on halogens and nitrate, because laboratory and field studies have clearly shown that both reactive halogens and nitrogen oxides are emitted from irradiated snow and ice. Liao and Tan (2008) integrated simplified chemistry in a 1-D snow model aiming to simulate the formation of HONO in the snow during a 6-day period at the South Pole using prescribed and constant concentrations of nitrate and nitrite. The chemical reactions included the photolysis of NO − 3 assumed to form directly HONO and the photolysis of HONO as its only sink.…”
Section: Chemical Processes In Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of photochemistry in surface snow and ice has focused on halogens and nitrate, because laboratory and field studies have clearly shown that both reactive halogens and nitrogen oxides are emitted from irradiated snow and ice. Liao and Tan (2008) integrated simplified chemistry in a 1-D snow model aiming to simulate the formation of HONO in the snow during a 6-day period at the South Pole using prescribed and constant concentrations of nitrate and nitrite. The chemical reactions included the photolysis of NO − 3 assumed to form directly HONO and the photolysis of HONO as its only sink.…”
Section: Chemical Processes In Modelsmentioning
confidence: 99%
“…A similar approach was used to reproduce laboratory experiments investigating the photolysis of nitrate in snow (Honrath et al, 2000;Dubowski et al, 2002;Jacobi and Hilker, 2007;Bock and Jacobi, 2010;Jacobi, 2011). Over time the applied chemical mechanisms were upgraded from very simplified mechanisms as presented by Liao and Tan (2008) to the most advanced model to date presented by Thomas et al (2011). The most advanced model extended an existing atmospheric 1-D chemistry model including gas-phase, aqueous-phase, and heterogeneous chemistry using additional layers to represent chemical processes in the snow.…”
Section: Conclusion About Chemistrymentioning
confidence: 99%
“…Testing this theory requires the building of a numerical model which represents nitrate recycling at the airsnow interface and describes the evolution of the nitrogen and oxygen stable isotopic composition of nitrate with various constraints from key environmental variables such as the solar zenith angle and the available UV radiation. Various models have been developed to investigate the physical and chemical processes involving nitrate in snow and their impact on the atmospheric chemistry in Antarctica (Wang et al, 2007;Liao and Tan, 2008;Boxe and Saiz-Lopez, 2008) and in Greenland (Jarvis et al, , 2009Kunasek et al, 2008;Thomas et al, 2011;Zatko et al, 2013). Those models are adapted to short time periods (hours to days, typically) and focus on processes at play in the atmosphere and in the nearsurface snowpack.…”
Section: Introductionmentioning
confidence: 99%
“…9 Perhaps because of evidence such as this, the freezing-point depression model is widely used in numerical models of ice and snow (photo)chemistry to describe solute concentrations in the LLRs of ice. [12][13][14][15][16][17] Understanding the composition of LLRs is essential, in part, because values of the freeze-concentration factor can significantly influence the (photo)chemistry of trace species on ice and snow. 2,18 For some reactions the chemical behavior in LLRs is similar to liquid-phase chemistry.…”
Section: Introductionmentioning
confidence: 99%